Exploratory Work for future Decision Support System using the Water Energy Food Nexus in the Aral Basin - Verbist, Joren; Akramkhanov, Akmal (2023)
This document aims at providing the necessary data, which are in this case Sustainable Land Management (SLM) practices, as preparation for a still to-be-determined Decision Support System (DSS) regarding water-energy-food-ecosystem in Central Asia through the NEXUS gains initiative of CGIAR. There are five main chapters to this document: 1. The goals and impacts of the CGIAR nexus initiative are briefly summarized. During this, the relations to DSS are described. 2. A brief study on DSS literature to find insights on what options there are, what data is required, and which users are benefitted. This offers support for the decision on a DSS, that is ought to be made in the future. Additionally, it provides a section on agri-DSSs. 3. A brief study on the nexus to understand which characteristics of a SLM are relevant to the nexus hence relevant for a DSS. A separate section is dedicated to each aspect of the nexus. 4. A synthesis of the nexus and DSS results in the rationale of a template that is useful for a potential future DSS specified on the nexus. In other words, this chapter explains why and how certain information of SLMs should be captured. 5. The template